MENINGKATKAN MINAT KUNJUNGAN ULANG MELALUI EMPATI : PERAN MEDIASI KEPUASAN PELANGGAN DAN CITRA - Kusworo, Edi; Nurcholis, Lutfi (Jurnal Pijar, 2024)
The purpose of this study is to determine the effect of empathy on return visit interest, the effect of empathy on customer satisfaction, the influence of empathy on image, the effect of customer satisfaction on revisit interest, the influence of image on revisit interest, the influence between empathy on revisit interest mediated by customer satisfaction and image. This research is a quantitative research. A sample of 150 respondents was randomly taken by interviewing and filling out questionnaires from visitors to the UPTD Jati Health Center, Kudus Regency. This research uses validity testing, reliability test and Structural Equation Modeling (SEM) analysis. The results of the study obtained 1) empathy has a positive effect on customer satisfaction. 2) Empathy has a positive effect on image. 3) Empathy has a positive effect on revisit interest. 4) Customer satisfaction has a positive effect on revisit interest. 5) Image has a positive effect on revisit interest. 6) The indirect influence between empathy on revisit interest with customer satisfaction and image as an intervening variable is proven to have a role because the indirect influence is greater than the direct influence with a value of 0.585.